Arm's Length Principle Analysis on Tax Avoidance through Transfer Pricing Post- Pandemic (Covid-19): A Proposed Study - ., Natalina; ., Apollo (KnE Social Sciences, 2023)
The Covid-19 pandemic has forced society to adapt to technological advancement and decision-making behavior in corporate management. In response, companies implemented transfer pricing strategy to ease the tax burden in order to optimize expenditure efficiency and maximize profitability. Besides its commonality among multinational companies, researchers observed that transfer pricing had been utilized significantly between related domestic companies, which may bring potential loss of state tax revenue. On the other hand, in principle, transfer pricing is legal and tax-wise permitable as long as it applies the arm’s length principle. This research was conducted in the form of case study with the objective to analyze the application of arm’s length principle on tax avoidance activity through transfer pricing between domestic companies by exploring its theoretical model. The analysis comprises five methods, namely the price comparison method between independent parties, the resale price method, the cost-plus method, the profit-sharing method, and the transactional net profit method. The evaluation of a company’s arm’s length principle can be utilized as a basis for recommendation, both for related companies to optimize tax planning and for policymakers to mitigate the risk of losing state revenue. This study is imperative in understanding post-Covid-19 impact on corporations as a mean of adaptation and going concern– specifically on how transfer pricing among specially-related domestic companies have become a cost-cutting effort. This study is expected to bring guidance for the following researches and contribution for government in overcoming the potential rise of domestic transfer pricing postpandemic. Keywords: arm’s length principle, domestic company, transfer pricing, tax avoidance